THE INFLUENCE OF RELIGIUS AND EMPATHY ON ALTRUISTICS IN PRIVATE ISLAMIC HIGH SCHOOL STUDENTS, UISU SIANTAR PROJECT - Rafika Fadilah Harefa; Siti Aisyah; Amanah Surbakti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research method uses quantitative methods. The aim of this research is to determine the influence of religiosity on altruistic behavior, to determine the influence of empathy on altruistic behavior, and to determine the influence of religiosity and empathy on altruistic behavior. The population was 115 and the sample was 115 students with a total sampling technique. Based on the results of the multiple regression test, there is a significant influence between religiosity and altruism as seen from the value of the terminant coefficient (R2) which has a value of 0.178, meaning that religiosity at the school contributes 17.8% to the altruism of students at UISU Siantar High School, then there is an influence The significant difference between empathy and altruism can be seen from the diterminant coefficient (R2) which has a value of 0.168, meaning that the empathy of students at this school contributes 16.8% to the altruism of UISU Siantar High School students. Based on the results of the multiple regression analysis test, there are results that there is a significant influence between religiosity and empathy on altruism as seen from the value of the terminant coefficient (R2) which has a value of 0.505, meaning that the student's religiosity and empathy contribute 50.5% to the altruism of high school students. UISU Siantar.